Listening to Women: Understanding and Challenging Systems of Power to Achieve Reproductive Justice in South Carolina. (10th April 2020) - Smith, Ellie; Sundstrom, Beth; Delay, Cara
Abstract: South Carolina women, especially low‐income women and women of color, face greater disparities in reproductive health outcomes, including low birth weight, preterm delivery, infant mortality, and maternal mortality, than do women nationally. The purpose of this study was to utilize a reproductive justice framework in which reproduction is considered a woman‐centered experience (as opposed to a social issue to be solved) to understand the reproductive experiences of women in South Carolina. We conducted 70 in‐depth interviews with women aged 19–78 years and analyzed these interviews using a constant comparative method. Study findings revealed that participants faced the consequences of oppressive systems of power when accessing reproductive health care, including high costs and lack of adequate health insurance coverage. Participants recognized the complexity of navigating reproduction in a conservative social context (i.e., South Carolina), further "compounded" by their gender and race. Women of color specifically noted challenges to reproductive care based on historical injustices and discrimination, including racial bias in hospital settings and aversion to certain contraceptive methods (e.g., IUD). Participants described the need to exercise reproductive autonomy and to have a "voice" in order to make desired lifestyle choices (e.g., career, motherhood) to overcome these challenges. Study findings evidence the women‐centered experience of reproduction within a specific sociogeopolitical context in order to uncover the challenges and opportunities to improving women's reproductive health in South Carolina.